Heavy metals in tap water from 32 Turkish cities - (:unkn) unknown (Scibulcom Ltd., 2016)
In the modern changing world exposure to heavy metals in tap water became a very important concern for the human health. In this view, tap water quality is checked against a range of national and international standards to minimise the risks to human health. Therefore, the aim of this study was to ascertain whether there was a risk to human health from metal contamination in tap water in Turkey or not. Samples of tap water were collected from 32 cities in Turkey and were analysed for the range of metals (Al, Fe, Cu, Co, Cr, Mn, Pb, Ni, and Zn) by ICP-MS. Comparison of results showed that none of the metal concentrations exceeded the Turkish, EU, USEPA, WHO, or FAO drinking water standards. The values obtained were generally significantly lower than the drinking water standards except few data. These findings indicate that there is no significant threat to human health from these metals in tap water in Turkey. Results not only point out a representative picture of heavy metal concentrations in drinking water from domestic taps at the national level but also provide valuable additional information that can be used to support assessment of potentially toxic effects on human health. © 2016, Scibulcom Ltd. All rights reserved.
Keywords: Contamination; Health; Heavy metal; ICP-MS; Tap water